A Literature Review on Multimedia-Based Qur’anic Learning for Generation Z - Ababil, Intan Meida; Okazani, Rechi Tri; Seftiani, Verly Tri; Syafutri, Tania; Utami, Intan (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
The rapid advancement of digital technology has significantly influenced educational practices, including Qur’anic learning for Generation Z. This literature review examines the characteristics and learning preferences of Generation Z, the forms and effectiveness of multimedia used in Qur’anic education, as well as the pedagogical impacts and challenges associated with multimedia-based learning. The reviewed studies indicate that Generation Z learners demonstrate a strong preference for visual, interactive, and technology-supported learning environments that promote engagement, autonomy, and immediate feedback. Various multimedia forms, such as instructional videos, mobile applications, digital Qur’an platforms, and interactive learning media, have been shown to enhance motivation, comprehension, and memorization of Qur’anic content when appropriately designed. Pedagogically, multimedia integration supports active learning, learner-centered instruction, and differentiated teaching approaches in Qur’anic education. However, challenges remain, including unequal access to technology, limited digital competence among educators, and the risk of reduced spiritual depth if pedagogical guidance is insufficient. The review concludes that multimedia-based Qur’anic learning holds considerable potential for Generation Z, provided that technological integration is aligned with sound pedagogical principles and the spiritual objectives of Qur’anic education.